Language Reflects Hate: Dysphemism Analysis of Incest Cases In Comments Column of CNN Indonesia’s Instagram - Panjaitan, Indra Purnawan; Pujiono, Mhd. (STAIN Majene, 2025)
This study investigates the use of dysphemism in public reactions to news about incest cases posted on the Instagram account @CNN Indonesia. The purpose of this study is to identify and analyse the types of dysphemism employed by netizens, based on Allan and Burridge’s (2006) theoretical framework. This study used a qualitative design with a descriptive model to analyze 155 comments posted on Instagram account @CNN Indonesia between January to May 2025. Data were collected through the observe and note method (Sudaryanto, 2015), then examined using Allan and Burridge (2006) framework of dysphemism types, applying both matching and distributional methods. The findings revealed seven categories of dysphemism: swearing and obscene language, non-derogatory profanity, comparisons between humans and animals, taboo terms, epithets, mockery of mental or physical conditions, and borrowed dysphemism. Among these, obscene language was the most prevalent type, comprising for 73.7% of the data, indicating that vulgar expressions serves as a primary channel for anger or resentment in public discourse regarding incest cases. This study shows that dysphemism is a crucial linguistic tool used by netizens to express anger and hatred in response to incest cases, which not only functions as verbal aggression but also as a social mechanism for channelling collective emotions in digital spaces. The results underscore the importance of fostering linguistic awareness through digital literacy initiatives, public awareness campaigns, and education programs in schools and universities, as well as by strengthening the role of media institutions in moderating public communication, particularly in societies with high social media engagement where language use profoundly shapes public moral and social norms.